ASSESSMENT METHODS FOR EARTHQUAKE-INDUCED VULNERABILITY IN BUILDING STRUCTURES - Hoca, Yasemin; Cafer, Cansur (International Scientific Journal Vision, 2025)
Seismic risk is one of the most researched topics in recent years. The negative consequences that earthquakes can cause, damage or losses, which can occur directly or indirectly, is defined as seismic risk. Strategies and methodologies for seismic risk assessment aim to reduce economic and social losses due to earthquakes. Assessment of seismic risk and seismic vulnerability of the existing building stock is essential for setting priorities in long-term prevention policies. The purpose of the assessment is to calculate the probability of damage that any group of buildings may experience during an earthquake. Various studies have been conducted so far and different methods have been proposed to assess the vulnerability of structures. Methods for assessing seismic vulnerability are used from individual buildings to large urban areas. To choose an appropriate method, the purpose of the research, the scope of the work, the approach to obtaining information should be taken into account. available resources and computational effort. This paper provides an overview of the primary methodologies used to assess the seismic vulnerability of buildings, including empirical, analytical, and hybrid approaches. Each method is examined in terms of its applicability, required data, computational demand, and accuracy